Shift In Recruitment Methods and Processes In The Digital Era (Systemic Literature Review) - Yanti, Ria Rahma; Theodora, Berta Dian (Yayasan Meira Visi Persada, 2025)
Digitizing the recruitment process becomes a difficult process when there is resistance from management and HR managers to new systems, especially when technology adoption is slow or even fails. Therefore, understanding the development and impact of digitizing the recruitment process through the use of intelligence technology is one form of technology adoption. The SLR method will collect, assess, and synthesize various studies relevant to the topic, thereby providing a comprehensive picture of the digitization of the recruitment process. The AI-based recruitment process can filter thousands of applicant data more quickly and objectively, creating a transparent and modern process, and reducing recruitment time by up to 75%, with a significant increase in candidate diversity.